2018
DOI: 10.3389/fpsyt.2018.00644
|View full text |Cite
|
Sign up to set email alerts
|

Anaerobic Exercise Training in the Therapy of Substance Use Disorders: A Systematic Review

Abstract: Background: In the past 3 decades, there has been an increase in the number of studies assessing exercise as a form of treatment for substance use disorders (SUDs). While a variety of substance types and outcomes have been assessed, exercise intensities have never been systematically examined. Consequently, it remains unclear whether particular forms of exercise are better suited to the treatment of these populations. Anaerobic exercise has been shown to have positive effects in populations with psychiatric di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(28 citation statements)
references
References 105 publications
1
23
0
2
Order By: Relevance
“…One meta-analysis [34] In that meta-analysis, control conditions included TAU, behavioural therapy, table football, computer games, occupational therapy and wait list. Similar findings were evident for these outcomes in another meta-analysis [80] (AMSTAR = 5, AMSTAR+ = 3), but no effect was found for depressive symptoms from aerobic exercise across five RCTs. A meta-analysis of seven RCTs [33] (AMSTAR = 5, AMSTAR+ = 3) of aerobic exercise and 292 people with schizophrenia spectrum disorder found that exercise improved global cognition versus control conditions which included table football alone (N = 1), occupational therapy (N = 1) and TAU (N = 5) (g = 0.412, 95% CI 0.19-0.64, p < 0.001).…”
Section: Schizophrenia Spectrum/serious Mental Illnesssupporting
confidence: 79%
See 1 more Smart Citation
“…One meta-analysis [34] In that meta-analysis, control conditions included TAU, behavioural therapy, table football, computer games, occupational therapy and wait list. Similar findings were evident for these outcomes in another meta-analysis [80] (AMSTAR = 5, AMSTAR+ = 3), but no effect was found for depressive symptoms from aerobic exercise across five RCTs. A meta-analysis of seven RCTs [33] (AMSTAR = 5, AMSTAR+ = 3) of aerobic exercise and 292 people with schizophrenia spectrum disorder found that exercise improved global cognition versus control conditions which included table football alone (N = 1), occupational therapy (N = 1) and TAU (N = 5) (g = 0.412, 95% CI 0.19-0.64, p < 0.001).…”
Section: Schizophrenia Spectrum/serious Mental Illnesssupporting
confidence: 79%
“…Following the full-text screening, a total of 27 articles were included. This included 16 meta-analyses of 152 RCTs in people with clinical disorders [33,34,[57][58][59][60][61][62][63][64][65][66][67][68][69][70] and 11 further systematic reviews in people with elevated symptoms and areas not covered by the existing meta-analyses [71][72][73][74][75][76][77][78][79][80][81]. The search results including reasons for exclusion are displayed in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The effect of exercise on withdrawal symptoms, anxiety, and depression was not moderated by the type of substance used. Colledge et al [ 30 ] reviewed the effects of anaerobic exercise on SUDs. The results were mixed, with some evidence of a positive effect on abstinence from nicotine.…”
Section: Introductionmentioning
confidence: 99%
“…To date, many articles on drug rehabilitation have talked about bene ts of moderate intensity continuous training (MICT). However, future research in the eld of exercise intervention should focus on using anaerobic exercise as an intervention to explore whether there is a dose-effect relationship to inhibit relapse (16). Many studies compared the effect of HIIT and MICT.…”
Section: Introductionmentioning
confidence: 99%